EXPLORING THE SUBCONSCIOUS DECISION MAKING IN NEUROMARKETING RESEARCH USING EYE TRACKING TECHNIQUE - Azman, H.S.; Amin, M.K.M.; Wibirama, S. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
This manuscript investigates the relationship of the effects and cognitive consumer purchase behaviors when making decisions. The study of consumer purchase behavior, which is known today as Neuromarketing, is one of the emerging multidisciplinary fields that link studies such as psychology, cognitive science, business planning, marketing and electronics systems. In contrast, traditional marketing business only based consumers’ responses on surveys with no direct quantification of their behavior. Hence, the study objectively focused on tracking the gazing behavior to measure and analyze its correlation to the behavior of the mind. We further investigate to determine the subconscious of consumer behavior in decision making and their purchasing process. In this experiment, the Tobii TX300 eye tracker was used to track and record the eye gaze. Sixteen mentally and physically healthy participants took part in this experiment. Men and women clothes collections from online shopping were chosen as the stimuli. The gaze behavior of each individual was observed and analyzed. A post experiment questionnaire was given to the participants to confirm their subconscious’ decision. The results showed that the gazing behavior of participants were significantly and subconsciously influenced by the bold, highlighted, and big elements of each stimulus. Hence, most of the respondents have their own decision when purchasing a product which does not depend on the amount of their eye-fixation on a product.